GEOLOGICAL MONUMENTS: ECOLOGICAL ASPECTS - NESTEROVSKYI, V.; KRYNYTSKA, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Mind changes of the geological heritage of Ukraine is analyzed. Criteria of estimation of Ukrainian geological monuments is allocated.